A six-week resistance training program does not change shear modulus of the triceps brachii - Akagi, R.; Shikiba, T.; Tanaka, J.; Takahashi, H. (Journal of Applied Biomechanics, 2016)
We investigated the effect of a 6-week resistance training program on the shear modulus of the triceps brachii (TB). Twentythree young men were randomly assigned to either the training (n = 13) or control group (n = 10). Before and after conducting the resistance training program, the shear modulus of the long head of the TB was measured at the point 70% along the length of the upper arm from the acromial process of the scapula to the lateral epicondyle of the humerus using shear wave ultrasound elastography. Muscle thickness of the long head of the TB was also determined at the same site by ultrasonography used during both tests. A resistance exercise was performed 3 days a week for 6 weeks using a dumbbell mass-adjusted to 80% of the 1-repetition maximum (1RM). The training effect on the muscle thickness and 1RM was significant. Nevertheless, the muscle shear modulus was not significantly changed after the training program. From the perspective of muscle mechanical properties, the present results indicate that significant adaptation must occur to make the TB more resistant to subsequent damaging bouts during the 6-week training program to target the TB.